Infrastruktur dan Produktifitas Pembangunan di Kecamatan Telluwanua, Kota Palopo, Sulawesi Selatan - Yashinta Kumala Dewi Sutopo; Ahmad Fauzi Budjang; Regita Chahyani Abdul Gani; Rizkiyah Amaliah Fadila; Syifa Beby Alisha; Azizah Putri Abdi (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2020)
This research is a community dedication activity which facilitate and simulate interaction between the research team with the society and local Government of Telluwanua District, Palopo City, which aimed to determine the quality of existing infrastructures, the economic productivity, and government programs. This research was conducted from February to May 2019 (3 months). The data and information were collected through observation and interviews with the staff from district authority, industrial office and spatial planning office, and local inhabitants such as households, workers, fishers, farmers, gardeners, and street sellers. The field observation showed that Telluwanua District has all basic facilities and infrastructure but the quantity and quality still needs to be improved. The most productive commodities developed by the local inhabitants are rice, cacao, palm oil, seaweed, and aquaculture. Ricefield in Telluwanua District is considered as one of the regional rice barns. Up to now, the local industry has successfully produced various ready eat/use cocoa-based products and a cooking oli of Boka brand. Tori cake and other home industrial products are among sources of daily income of the local household. The local government built a Community Creative Industry (IKM) equipped with essential tools, machines, training programs, and gallery functioned as exhibition, promotion, and selling place for all home industrial creative products.